L’autoconfrontation croisée comme instrument d’action au travers du dialogue - Julie Duboscq; Yves Clot (Revue d'anthropologie des connaissances)
In this article we show how the method of crossed self-confrontation can be used to develop work activities through a clinic of the participants’ dialogic activity. We first present three dialogue’s potentialities based on a bakhtinian and vygotskian theoretical framework: discovering the deepness of the ‘dialogue’s real’ under the speech and gestures conducted, addressing potentially three recipients and questioning reality. These potentialities are exploited in our methodological approach which aims at enlarging a dialogue among the professionals and ‘inside’ them in order to develop their work activity. As one step within this methodological approach, the method of crossed self-confrontation uses the dialogue as a tool. Eventually we study a dialogue excerpted from a crossed self-confrontation between two workers. These data come from a research led in the construction sector. We highlight movements in the discourse object and statements addressed to different recipients. These indicate and stimulate a development in the protagonists’ thought. We also make the assumption of cross-functional relationships between dialogue and action. For example, new gestures accompanying speech as argument are made concretely later.